Effect of Regular Exercise on Anxiety and Self-Esteem Level in College Students - Zahra Hamidah; Putri Teesa Santoso; Radenmas Haryadi Karyono (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Regular exercise is often presented as an effective tool to influence the psychological aspect of a human being. Recent studies show that anxiety and self-esteem are the most important psychological aspects especially in college students. This study aimed to determine the differences of anxiety and self-esteem level between students who joined and did not join regular exercise program, Pendidikan Dasar XXI Atlas Medical Pioneer (Pendas XXI AMP), in the Faculty of Medicine, Universitas Padjadjaran.Methods: A cross-sectional comparative study was carried out to 64 students who joined and did not join Pendas XXI AMP. Thirty six students (12 females and 20 males) who joined Pendas XXI AMP participated in aerobic and anaerobic exercise sessions lasting for 30 minutes per session, three times in 5 months. The control group was 32 students who did not join Pendas XXI AMP, with matching gender composition as the case group (12 females and 20 males). Two questionnaires, Zung Self-Rating Anxiety Scale questionnaire and Rosenberg’s Self-Esteem Scale questionnaire, were administered to both groups. The data were analyzed using chi-square test (α=0.05).Results: : There were statistically significant differences in anxiety level (p=0.016) and self-esteem level (p=0.039) between case and control groups. The students who joined Pendas XXI AMP have lower anxiety and higher self-esteem levels.Conclusions: Planned, structured, and repeated physical activities have a positive influence in anxiety and self-esteem levels. DOI: 10.15850/amj.v2n3.517